Find the product.
(n + 8)(n - 2)
n2 - 6n - 16
n2 + 6n - 16
n2 - 6n + 16

(n + 8)(n - 2) = n^2 + 6n - 16

s

Question

Asked 3/5/2012 4:58:20 PM

Updated 2/24/2014 3:21:49 PM

1 Answer/Comment

Rating

8

(n + 8)(n - 2)

= n^2 + 6n - 16

= n^2 + 6n - 16

Added 2/24/2014 3:21:49 PM

This answer has been confirmed as correct and helpful.

(n + 8)(n - 2) **Weegy:** 1 - n = 8/11, n = 8/11 + 1, n = 1 8/11 or 19/11 **User:** Choose the product.
a3b2 · 4ab3
4a3b5
4a3b6
4a4b5 (More)

Question

Not Answered

Updated 2/13/2014 9:18:04 PM

1 Answer/Comment

(n + 8)(n - 2)

= n^2 - 2n + 8n - 16

= n^2 + 6n -16

= n^2 - 2n + 8n - 16

= n^2 + 6n -16

Added 2/13/2014 9:17:58 PM

This answer has been confirmed as correct and helpful.

Factor k2 + 13k + 12.
(k + 2)(k + 6)
(k + 3)(k + 4)
(k + 12)(k + 1)

Question

Updated 3/30/2014 9:47:10 PM

1 Answer/Comment

Factor 360t + 10t3 - 120t2. User: How many terms are in the polynomial abcd + e - fg + h2?
one
two
three
four **Weegy:** 4 **User:** Divide x4 + 7 by x - 3.
x³ - 3x² - 9x - 27 R 88
x³ + 3x² + 9x - 27 R -74
x³ + 3x² + 9x + 27 R 88 **User:** Factor 9b2 - 4.
(3b + 1)(3b - 4)
(3b + 2)(3b - 2)
(3b - 2)(3b - 2) **Weegy:** (a-b)(r+s). please rate this answer, **User:** Factor 3x2 - 15x - 42.
3(x - 2)(x - 7)
3(x - 2)(x + 7)
3(x - 7)(x + 2) **Weegy:** B.3(x - 2)(x + 7). 3 times (x-2) = (3x-6) multiplied by (x + 7) = 3x^2 - 15x-42. **User:** Factor 3x2 - 15x - 42. **User:** Select the correct difference.
-3z7 - (-5z7)
2z7
8z14
-2z7
2z (More)

Question

Updated 5/26/2014 1:07:31 PM

5 Answers/Comments

360t + 10t^3 - 120t^2 = 10t^3 - 120t^2 + 360t = 10t(t^2 - 12t + 36) = 10t(t - 6)^2

Added 5/26/2014 1:02:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/26/2014 1:08:57 PM]

x^4 + 7 divided by x - 3 is x³ + 3x² + 9x + 27 R 88

Added 5/26/2014 1:03:39 PM

This answer has been confirmed as correct and helpful.

9b^2 - 4 = (3b + 2)(3b - 2)

Added 5/26/2014 1:04:28 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/26/2014 1:09:46 PM]

3x^2 - 15x - 42 = 3(x^2 - 5x - 14) = 3(x - 7)(x + 2)

Added 5/26/2014 1:06:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/26/2014 1:10:06 PM]

-3z^7 - (-5z^7) = -3z^7 + 5z^7 = 2z^7

Added 5/26/2014 1:07:25 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/26/2014 1:10:37 PM]

9a4 - b2 **Weegy:** 9a^4 - b^2 = (3a^2 - b)(3a^2 + b). **User:** Factor completely.
vwx + wxy - xyz
x(vw - wy + yz)
x(vw - wy - yz)
x(vw + wy - yz) (More)

Question

Updated 7/16/2015 6:05:27 AM

1 Answer/Comment

vwx + wxy + xyz

= x(vw + wy + yz)

= x(vw + wy + yz)

Added 7/16/2015 6:03:05 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/16/2015 6:05:31 AM]

34,173,311

questions answered

There are no comments.